PENGARUH FAKTOR INTERNAL DAN FAKTOR EKSTERNAL TERHADAP INDEPENDENSI AUDITOR (Studi pada Kantor Akuntan Publik di Surabaya) - Drs. Ec. Hanny Wurangian, M.Si., Ak.; Dr. Muslich Anshori, M.Sc., Ak. (EKUITAS (Jurnal Ekonomi dan Keuangan), 2006)
Public accountant role and it position is creticized by society, especially for some cases involved large company and big certified public accountant, such happened in United States few years ago. In Indonesia, there are some cases which still cause pro and contra in public. In those cases, public accountant professionalism is questioned. As we know, the most important aspect, which public accountant must maintain is trust from society as their user.In this research, we analyzed auditor independency aspect and some factors, such as: quality of auditor, auditor financial wealth, auditor-clients relationship, client size measure, audit duration, audit relation duration, and adherence to existing rule and regulation at certified public accountant in Surabaya. Population in this research is auditors and partners who signing audited financial statement (audit report) that work at certified public accountant office in Surabaya. In Surabaya, there are 54 CPA Offices or 77 auditors and partners. All of those 77 auditors and partners acted as respondent and analysis units in this research. Thus, the data collection was done by census.Multiple Regression Model was used to test hypthesis which said that quality of auditor, auditor financial wealth, auditor-clients relationship, client size measure, audit duration, audit relation duration, and adherence to existing rule and regulation, both collectively and partially, affected to auditor independency at CPA Office in Surabaya.This research show that quality of auditor, auditor financial wealth, auditor-clients relationship, client size measure, audit duration, audit relation duration, and adherence to existing rule and regulation, collectively, affect to auditor independency at CPA Office in Surabaya. And only 3 or 7 tested variables, which is quality of auditor, auditor-clients relationship, and audit duration, partially, affect to auditor independency, which the most affected variable is auditor-clients relationship.